Mengintegrasikan Kearifan Lokal ke dalam Literasi Iklim: Praktik Budaya dan Ketahanan Iklim di Indonesia - Firnadi, Andrean Ardhitya (Journal of Geographical Sciences and Education, 2025)
Amid escalating climate risks, climate literacy is crucial for enabling community resilience. In Indonesia, the core principles of climate literacy are embedded in long-standing local wisdom across diverse cultural landscapes. This study employs a qualitative, literature-based approach to explore how indigenous practices, ranging from forest and coastal conservation to water, soil, and disaster management, embody climate knowledge. Thematic analysis reveals that these practices reflect adaptive, context-specific strategies aligned with sustainability science. However, formal climate policies often overlook or marginalize traditional knowledge due to epistemic biases. The findings advocate for integrating local wisdom into climate education and governance through participatory and co-productive models. Such integration not only validates indigenous knowledge but also enhances the cultural relevance and effectiveness of climate strategies. Recognizing local wisdom as a legitimate foundation for climate literacy offers a path toward more inclusive, resilient, and grounded responses to the climate crisis